(3GKQ LhOI GdHjGfGJ ai GdJfHD HcaGAI GdbWGY GdNGU GdeUQi (B/ s - (3QTG eMeO fHjd GdSjO s; (3GeGfi ehSi eMeO (B: s; (3jGSejf eMeO EHQGgje (B: s ((3GdbGgQI (B: s (3QTG eMeO fHjd GdSjO (B: s, 2020)
(3JgOa gPg GdOQGSI Edi bjGS LhOI GdHjGfGJ aj GdJYOGO GdGbJUGOj HefTBJ GdbWGY GdNGU GdeUQi(B: (3hOQGSI CKQ LhOI GdHjGfGJ Ydi GdfeGPL GdEMUGFjI(B. (3hSha jJe GdGYJeGO aj OQGSI Jdc GdeTcdI Ydi HjGfGJ GdJYOGO GdGbJUGOj defTBJ GdbWGY GdNGU GdJj jUOQgG GdLgGR GdeQcRj ddJYHFI GdYGeI hGdEMUGA HUa`I eSJeQI(B: (3MjK jJe GSJNOGe ebGjjS GdLhOI GdJj bnqOeJgG dbjGS LhOI eDTQGJ GdJYOGO GdGbJUGOi (B: (3ddhUhd Edi Mdhd JgOa Edi JMSjf LhOI GdHjGfGJ GdEMUGFjI aj eUQ hGdJYQa Ydi eOi JWHjb GdLgGR GdeQcRj ddJYHFI GdYGeI hGdEMUGA deYGjjQ GdLhOI(B.(3hdJMbjb CgOGa GdOQGSI Je CNP HYV GdeDTQGJ GdNGUI HGdJYOGO GdGbJUGOj dHYV GdbWGYGJ eKd (B((3bWGY GdUfGYGJ GdJMhjdjg (B{u(32013(B} (3GdJTjO hGdHfGA (B{u(32013(B} (3JLGQI GdLedg hGdJLRFjI (B) (3GfWdGkbG ef CgejJgG(B: (3hJe JWHjb ebGjjS GdLhOI hJhUdJ GdOQGSI Edi Cf GdLgGR jbhe HJWHjb eYGjjQ GdLhOI heHGOFgG HTcdgG GdYGe; ef MjK GdGSJbdGd Gdegfj(B: (3hGdJahjV dLeY GdHjGfGJ(B: (3hSQjI GdHjGfGJ GdaQOjI(B: (3hcPdc jWHb GdeYGjjQ GdNGUI HGdeNQLGJ GdEMUGFjI; ef MjK GdUdI HGdhGbY hGdSQYI hObI GdhbJ aj GdfTQ(B: (3hdcf HGdfSHI dJWHjb ebGjjS GdLhOI GdebJQMI jJVM Cf gfGc GNJdGaGJ hJHGjkfG edMhkXG Hjf GdbWGYGJ(B:(3GdCeQ GdPj jOd Ydi YOe JWHjb eYGjjQ GdLhOI HGdTcd GdeWdhH habG debjGS GdLhOI GdebJQM s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddHMhK GdEMUGFjI (B- (3bSe GdEMUGA GdJWHjbj s
(3UOQ GjVG cbQU eOeLs
Keywords: (3LhOg GdHjGfGJ s; (3eYGjjQ heHGOF GdLhOI s; (3ebGjjS GdLhOg s